The greatest silence of the writing: Japanese aesthetic and sensibility in the poetry of Javier Sologuren - Vallejo Bulnes, Rafael (2016)
Javier Sologuren and Japan’s relationship was –in his own words– a passion in crescendo, which is manifested through different aspects in his literary work. This essay examines the career of the Peruvian author in order to determine the influence that Japanese lyric worked in his poetry; influence which is not only formal but also arising as a poetic and existential reflection, and –finally– leading to a curious poetic syncretism. In addition, it explores the distinctive way in which Sologuren approached the Japanese culture and the significant role the translation played by in this process.